1996
DOI: 10.1074/jbc.271.6.2979
|View full text |Cite
|
Sign up to set email alerts
|

Chimeric Vesicular Monoamine Transporters Identify Structural Domains That Influence Substrate Affinity and Sensitivity to Tetrabenazine

Abstract: The vesicular monoamine transporters (VMATs) 1 and 2 show close sequence similarity but substantial differences in apparent substrate affinity and drug sensitivity. To identify structural domains that determine these functional characteristics, chimeric transporters were constructed and their properties were analyzed in a heterologous expression system. The results implicate multiple regions in the recognition of serotonin and histamine and the sensitivity to tetrabenazine. Two domains of VMAT2, one extending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 27 publications
5
41
0
Order By: Relevance
“…The model is also supported by the work performed using chimeric VMAT1/VMAT2 proteins (44). Replacing TMD1 of VMAT1 with TMD1 of VMAT2 increased the affinity of the transporter for inhibitors and substrates to an intermediate level between VMAT1 and VMAT2.…”
Section: I]azik-and [mentioning
confidence: 49%
“…The model is also supported by the work performed using chimeric VMAT1/VMAT2 proteins (44). Replacing TMD1 of VMAT1 with TMD1 of VMAT2 increased the affinity of the transporter for inhibitors and substrates to an intermediate level between VMAT1 and VMAT2.…”
Section: I]azik-and [mentioning
confidence: 49%
“…129 Experiments employing a chimera of VMAT1 and VMAT2 indicate that 2 domains, TMD5 through TMD8 and TMD9 through TMD12, cooperate to confer the high-affi nity interaction of VMAT2 with TBZ and histamine. 130 In addition, the domain encompassing TMD3 and TMD4 infl uences serotonin affi nity but not histamine affi nity or TBZ sensitivity. 130 The domain encompassing TMD5 through TMD7 of VMAT2 in the context of N-terminal VMAT2 sequences reduces the apparent affi nity for serotonin but not histamine or the sensitivity to TBZ.…”
Section: Vmat2 Structure and Molecular Basis For Bindingmentioning
confidence: 99%
“…130 In addition, the domain encompassing TMD3 and TMD4 infl uences serotonin affi nity but not histamine affi nity or TBZ sensitivity. 130 The domain encompassing TMD5 through TMD7 of VMAT2 in the context of N-terminal VMAT2 sequences reduces the apparent affi nity for serotonin but not histamine or the sensitivity to TBZ. 130 Tyrosine 434 and aspartate 461 in TMD9 through TMD12 are identifi ed as being responsible for the high-affi nity interaction of TBZ, histamine, and serotonin, but not for DA.…”
Section: Vmat2 Structure and Molecular Basis For Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify domains responsible for these differences, we first expressed and analyzed a series of chimeric transport proteins (8). These chimeras retained function, and analysis showed that two major regions from VMAT2, one extending from transmembrane domain (TMD) 5 to the beginning of TMD8 (TMD5-8) and the other from the end of TMD9 through TMD12 (TMD9 -12), are apparently both required for the high affinity interactions characteristic of VMAT2 (8).…”
mentioning
confidence: 99%